It's just between girls: Negotiating the postfeminist gaze in women's 'looking talk'. (February 2016) - Riley, Sarah; Evans, Adrienne; Mackiewicz, Alison
Feminists have argued that women's bodies, appearance, and subjectivity are formed through a multitude of regulatory dispositif and disciplinary apparatus. One such disciplinary technique has been "looking", evidenced in work on the male gaze, disciplinary power, misrecognition, objectification, and indirect social aggression. But there remains a significant gap in the role of women's looking in subject formation, particularly within the context of a postfeminist sensibility. To address this gap a poststructuralist informed discourse analysis was performed on interviews with 44 white heterosexual British women (aged 18–36). Four discourses deployed by the participants when talking about looking between women were identified. These discourses were as follows: judgemental looking between women is pervasive; judgement is consumption oriented; women's looks are prioritised over men's, foregrounding a female gaze; and appearance is the vehicle to recognition. We conclude by highlighting the importance of a postfeminist gaze for understanding women's subjectivities, and how looking works in a postfeminist context to maintain regulation, anxiety, surveillance, and judgement.